ANALYSIS OF THE QUALITY SYSTEM AT THE ENTERPRISES OF RETAIL CHAINS - A. Dvoryankina; T. Rogulenko (Вестник университета)
The article classifies the standards and levels of the quality management system for retail chain enterprises. The main stages of building a quality system are described. The importance of introducing, maintaining and improving the quality management system in retail is substantiated. A new principle for use in drafting the document «Quality objectives» was suggested. The main mistakes in implementing the quality management system (QMS) was found. Key points of QMS analysis in each department are listed.